2012
DOI: 10.1111/j.1654-1103.2012.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Different plant trait scaling in dry versus wet Central European meadows

Abstract: Question Trait scaling relationships involve multiple trade‐offs and allometric constraints between the traits of co‐existing species. Alternative trait relationships, particularly between plant size and other traits, are expected in response to combinations of different biotic and abiotic filters. To what extent does the expected convergence in plant attributes to water shortage and disturbance produce different trait scaling relationships in dry vs wet meadows under various disturbance regimes? Locations One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
(152 reference statements)
1
31
1
Order By: Relevance
“…At the species level, increases (Jaramillo & Detling ; de Bello et al. ) and decreases in foliar N concentration (Pontes et al. ) have been reported in response to clipping, while SLA was found to be unaffected (Thorne & Frank ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the species level, increases (Jaramillo & Detling ; de Bello et al. ) and decreases in foliar N concentration (Pontes et al. ) have been reported in response to clipping, while SLA was found to be unaffected (Thorne & Frank ).…”
Section: Introductionmentioning
confidence: 99%
“…If co‐existing species are sufficiently different in their response of SLA and foliar N to management intensification, the alterations should have the potential to change not only trait‐based species rankings, but also the strength of expected between‐trait relationships (de Bello et al. ). If trait interrelationships were found not to be consistent across different sites and communities, this was mostly attributed to variation in sample size; however, Wright et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits have been demonstrated to be important indicators of plant strategies, since they reflect a fundamental trade‐off in plant functioning between rapid biomass production (high SLA, high LNC, low LDMC, low StDMC and low LCC) and the efficient conservation of nutrients (low SLA, low LNC, high LDMC, high StDMC and high LCC; Garnier et al, ; Pérez‐Harguindeguy et al, ). The δ 13 C isotope has been shown to reflect the water availability to plants (de Bello et al, ; Farquhar, Ehleringer, & Hubick, ), whereas the δ 15 N isotope has been shown to reflect the N availability to plants (Robinson, ).…”
Section: Methodsmentioning
confidence: 99%
“…Land use factors like mowing and fertilization determine the disturbance regime and soil fertility (Kotas et al, 2017), which are the key conditions for plant growth and thus for ITV. For instance, fertilization increases the specific leaf area (SLA) and leaf nitrogen content (LNC) and decreases leaf dry matter content (LDMC), while mowing decreases the height of plant individuals in consecutive years (de Bello et al, 2012;Pakeman, 2013;Pontes, Soussana, Louault, Andueza, & Carrére, 2007;Rose, Rubarth, Hertel, & Leuschner, 2013). These effects can be the result of either direct response of plants or they can also be driven by altered plant to plant interactions in response to land use induced changes in species composition (Díaz et al, 2007;Kotas et al, 2017;Le Bagousse-Pinguet et al, 2015;Lepš, 1999Lepš, , 2014.…”
Section: Introductionmentioning
confidence: 99%